2023
DOI: 10.1038/s41598-023-36707-y
|View full text |Cite
|
Sign up to set email alerts
|

Risk analyses of nocturia on incident poor sleep and vice versa: the Nagahama study

Abstract: Cross-sectional relationships between nocturia and sleep problems have been well evaluated but the risk association for each incidence is scarcely reported. This analysis included 8076 participants of the Nagahama study in Japan (median age 57, 31.0% male) and associations between nocturia and self-reported, sleep-related problems (poor sleep) were evaluated cross-sectionally. Causal effects on each new-onset case were analyzed longitudinally after 5 years. Three models were applied: univariable analysis, adju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Finally, studies had shown that watching TV for an extended period had negative impacts on health, such as reducing sleep duration or affecting sleep quality 24,25 . And a decrease in sleep quality is closely linked to experiencing nocturia 26 . Additionally, a correlation has been established between watching TV and an elevated risk of obesity, a factor conclusively linked to the severity of nocturia 21,27 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, studies had shown that watching TV for an extended period had negative impacts on health, such as reducing sleep duration or affecting sleep quality 24,25 . And a decrease in sleep quality is closely linked to experiencing nocturia 26 . Additionally, a correlation has been established between watching TV and an elevated risk of obesity, a factor conclusively linked to the severity of nocturia 21,27 …”
Section: Discussionmentioning
confidence: 99%
“…24,25 And a decrease in sleep quality is closely linked to experiencing nocturia. 26 Additionally, a correlation has been established between watching TV and an elevated risk of obesity, a factor conclusively linked to the severity of nocturia. 21,27 This study has several notable strengths, such as its national representativeness and the substantial sample size obtained from NHANES data.…”
Section: Discussionmentioning
confidence: 99%